Protective effects of α-ketoglutaric acid on palmitic acid-induced deterioration in sheep endometrial epithelial cells via ferroptosis inhibition - Bai, Ziyi; Fang, Qinyuan; Li, Shubin; Jia, Mengxuan; Zhang, Rongrong; Wang, Chunyu; Wu, Zhenli; Liu, Gang; Liu, Yongbin (Frontiers in Veterinary Science, 2025)
IntroductionEmerging evidence indicates that dysregulated palmitic acid (PA) homeostasis plays a key role in inducing lipotoxicity and cellular dysfunction in mammalian endometrial epithelial cells. While this phenomenon has been documented in bovine models, the underlying mechanisms of PA-induced toxicity in sheep endometrial epithelial cells (SEECs) remain poorly understood. Moreover, effective strategies to counteract PA-mediated damage in SEECs have yet to be fully explored.MethodsIn this study, we investigated the protective effects of α-ketoglutaric acid (α-KG), a central metabolic intermediate in the tricarboxylic acid (TCA) cycle, against PA-induced cellular impairment in SEECs. Functional assays were performed to assess changes in cell viability, proliferation, migration, lipid accumulation, cell cycle progression, DNA damage, histone trimethylation, and apoptosis. Integrated transcriptomic and metabolomic analyses were conducted to elucidate the molecular pathways involved.Results and discussionOur results demonstrated that α-KG markedly alleviated PA-induced cytotoxicity. Specifically, α-KG enhanced cell viability, restored proliferative and migratory capacities, promoted cell cycle progression, and attenuated lipid accumulation, DNA damage, histone trimethylation alteration, and apoptosis. Multi-omics profiling, supported by ferroptosis-specific assays, revealed that these cytoprotective effects were predominantly mediated through the suppression of PA-induced ferroptosis. Collectively, our findings provide novel mechanistic insight into the role of α-KG in mitigating lipid-induced cellular stress and establish its therapeutic potential as a metabolic modulator. This study not only advances our understanding of ferroptosis in reproductive cell biology but also opens new avenues for targeted interventions against lipotoxic damage in endometrial tissues.